Pengembangan Instrumen Asesmen Buku Kontrol Metode Tasmi’ Bilghoib di Asrama O Pondok Pesantren Ngalah Purwosari Pasuruan - Dian Indah Nur’Aini; Askhabul Kirom; Ali Muhtarom; Muhammada (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is in the background of the minimal control of the progress of the development of the Tahfidz Shelter O hostel and the minimum appreciation of the benefits of the hostel or hostel. This study aims to find out the effectiveness of assessment of the tasmi’ bilghoib method control book to improve the quality of health care of Tahfidz centers in the dormitory of the hostel. The type of research used is R&D (Research and Develop) with a 4D development model, which includes definition, design, development, and dissemination. Based on the test results of this study, it showed that 95% of the question indicators were very much in agreement with the presence of the tasmi’ bilghoib method control book and 5% disagreed with the existence of the control book, because this control book could be said to be very effective if used in the O Hall to improve the quality of references.